A preview of perennial grain agriculture: knowledge gain from biotic interactions in natural and agricultural ecosystems. Issue 12 (22nd December 2017) - Rasche, Frank; Blagodatskaya, Evgenia; Emmerling, Christoph; Belz, Regina; Musyoki, Mary K.; Zimmermann, Judith; Martin, Konrad
Abstract: Compared to their annual analogues, perennial grain cropping systems provide various beneficial attributes for the environment and ecosystem services related to resource use efficiency, soil erosion, and soil conservation. However, there is only limited understanding of the multiple biotic interactions in perennial cropping systems and their potential effects on the crop, involving plant growth‐promoting and pathogenic microorganisms, beneficial and detrimental faunal organisms below‐ and above‐ground, weeds, and overall biodiversity effects. We use information from studies carried out in managed and natural perennial systems of analogous structure such as perennial energy crop production systems and grasslands to highlight and specify biotic interactions and processes, which potentially constitute advantages and constraints in developing perennial grain cropping systems. Concerning the relevance of soil microorganisms and potential perennial crop breeding goals, we focus on a range of plant–microbe interactions in the rhizosphere involved in biofertilization, phytostimulation, and biological control of soil pathogens. We consider relationships within the faunal community emphasizing arthropod pests and their natural enemies, as well as crop–weed interactions. Based on these outcomes and in comparison with annual systems, we discuss and compile benefits, options, and limitations of management of crop‐associated biotic interactions and biodiversity, which might contribute to reproducible and sustainable effects of perennial grain crop productivity. We conclude that management strategies for perennial grain cropping systems depend much more on ecological processes and interactions operating in natural ecosystems than those in annual cropping systems. Consequently, the use of agrochemicals for pest, weed, and disease control, as well as the use of synthetic fertilizers, counteracts the principle functions of the system and would strongly degrade the potential of biotic benefits. We also found that there is only vague information on the long‐term productivity and cultivation period of perennial grain crops, the specific management operations of replacement, and the potential development and management of weed and pest populations. Overall, an advanced understanding of interactions between the crop and its biotic environment provides the opportunity to manipulate specific functional traits of crop‐associated organisms for improved management and crop productivity, but significant research challenges for implementation of perennial grain crops still remain.